Implementasi Algoritme Trivium Untuk Mengamankan Data Pada Protokol MQTT Menggunakan Perangkat Raspberry Pi - Alan Maulana Hamid; Ari Kusyanti; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
MQTT Protocol (Message Queuing Telemetry Transport) is widely used in wireless communication medium on IOT (Internet of Things). On the other hand, the use of wireless medium has a disadvantage. As an example, the data are highly vurnerable to eavesdropping (sniffing data). The dangerous impact of eavesdropping or sniffing is that the loss of security. Therefore, it is required to have a mechanism to ensure data security. Trivium algorithm is one of the cryptographic synchronous encryption cryptographic algorithms used to secure data and Trivium is tested well and Trivium is assigned as a stream cipher encyption algorithms by ISO/IEC 29192-3; 2012. Raspberry Pi is used as a publisher, subscriber and virtual machine as a broker. Publisher will encrypt the data before the data and topic are sent to the broker. Broker will forward the data to the subscriber that is subscribed. After the data is received by the subscriber, the data will be decrypted into plaintext. Here are the results of the study; keystream result to the vector test is valid, validation result of encyption and decryption is valid, the result of sniffing data of Wireshark shows that the data cannot be read by an unofficial authority, and the result of six functional systems showed that all of the functional work well, the result of the average time to produce keystream is that 0.034886725 seconds, encryption process is that 0.047045873 seconds and decryption process is that 0.053834003 seconds